Food allergy, safety and analytics - Tömösközi, Sándor; Hajas, Lívia; Langó, Tamás; Török, Kitti; Bugyi, Zsuzsanna (Acta Agraria Debreceniensis, 2012)
The food allergy is a hypersensitivity reaction against naturally occurring proteins in food. These types of disease can cause not only personal inconvenience to the patient but serious health, food safety and food analysis, social-economic problems. The only effective treatment for these illnesses is a life-long diet avoiding the allergenic foods or components of food. In the interest of the patients’ health 14 allergenic components must be labeled on the food packaging. To meet the requirement of regulation reliable and valid analytical methods are necessary which for the most allergenic foods are not available.